Infiltrasi dan Aliran Permukaan pada Agroforestri dan Kelapa Sawit - Austin Ullyta; Suria Darma Tarigan; Enni Dwi Wahjunie (Institut Pertanian Bogor, 2022)
Forest to oil palm plantations conversion has changed soil's physical properties significantly. It caused significant changes in the hydrological cycle and affects the water resources around the research site. One of the strategies that could minimize the negative impact of monoculture oil palm plantations is better plantation management by implementing a mixed cropping system (agroforestry). This study aims to analyze the infiltration, surface runoff, and surface runoff coefficient in agroforestry and monoculture oil palm. This observation was conducted in the oil palm plantation area of PT Humusindo Makmur Sejati, Bungku Village, Bajubang District, Batanghari Regency. The infiltration rate was calculated according to the Horton method, and the amount of runoff in agroforestry and oil palm monoculture used the soil conservation service-curve number method. The results showed differences in infiltration, surface runoff, and runoff coefficients between the agroforestry land and the monoculture oil palm. The highest infiltration is in A48, which is 42,00 cm/hour in the dry season and 18,00 cm/hour in the rainy season. The lowest runoff is in A23, which is 70.14 mm with a runoff coefficient of 0.04. The highest runoff occurred in S48 of 339.88 mm, with a runoff coefficient of 0.19. The differences in infiltration, surface runoff, and runoff coefficient in this study are affected by the vegetation density and the amount of litter. Keywords: agroforestry, infiltration, oil palm, runoff coefficients, surface runoff